Determination of cadmium in tobacco by solid surface fluorescence using nylon membranes coated with carbon nanotubes - Talio, María Carolina (2013)
A new methodology based on fluorescent signal enhancement of o-cresolphthalein (o-CPT) for traces of cadmium determination is proposed. The dye was retained on membrane filters in the presence of a micellar surfactant solution of carbon nanotubes (CNTs). All the experimental variables that influence both the preconcentration procedure and the fluorimetric sensitivity were carefully optimized. The calibration graph using zeroth order regression was linear from 6.5 ng L-1 to 5.65×105 ng L -1, with a correlation coefficient higher than 0.999. Under optimal conditions, the limits of detection and quantification were of 2 ng L -1 and 6.5 ng L-1. respectively. The proposed method showed good sensitivity and selectivity, with good tolerance to foreign ions, and it was applied to the determination of trace amounts of cadmium in leachate from cigarettes' tobacco samples with satisfactory results. The trueness of the recommended procedure was assessed through parallel analysis of the samples with electrothermal atomization atomic absorption spectrometry. This methodology represents an innovative and attractive application of membrane filters that enables metal traces determination by solid surface fluorescence.